2022
DOI: 10.1088/1361-6528/ac4c5f
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal methane coupling into liquid fuels with hydrogen evolution over nanocatalysts based on layered double hydroxide (LDH)

Abstract: The increasing energy and environmental problems have made clean energy-driven catalysis a hot research topic. Methane is an earth-abundant raw material but difficult to be converted by thermochemical processes. It is of great significance to seek novel strategies to convert methane into high value chemicals. Herein, we synthesize a series of transition metal catalysts based on layered double hydroxide precursors which were used for photothermal methane nonoxidative coupling reactions. The strong photothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Experimental data have shown that the evolution of active sites on the Pt 1 /MnO 2 occurs in the presence of CH 4 (Figure b). Therefore, it is necessary to reveal the evolution of active sites through CH 4 dissociation during DFT simulation. , The CH 4 dissociation process indicates that the barrier on Pt 1 /MnO 2 –R (0.92 eV) is lower than that on Pt 1 /MnO 2 (1.21 eV) because of the formation of OVs adjacent to Pt 1 . In the cleavage step of the C–H bond, the CH 4 transfers one H atom to the adjacent O atom. , As expected, after CH 4 is adsorbed on the surface of Pt 1 /MnO 2 , the H atom of CH 4 first generates a lattice hydroxyl with the neighboring lattice oxygen that is most easily activated, which coincides with our speculated OVs site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data have shown that the evolution of active sites on the Pt 1 /MnO 2 occurs in the presence of CH 4 (Figure b). Therefore, it is necessary to reveal the evolution of active sites through CH 4 dissociation during DFT simulation. , The CH 4 dissociation process indicates that the barrier on Pt 1 /MnO 2 –R (0.92 eV) is lower than that on Pt 1 /MnO 2 (1.21 eV) because of the formation of OVs adjacent to Pt 1 . In the cleavage step of the C–H bond, the CH 4 transfers one H atom to the adjacent O atom. , As expected, after CH 4 is adsorbed on the surface of Pt 1 /MnO 2 , the H atom of CH 4 first generates a lattice hydroxyl with the neighboring lattice oxygen that is most easily activated, which coincides with our speculated OVs site.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to reveal the evolution of active sites through CH 4 dissociation during DFT simulation. 48,49 The CH 4 dissociation process indicates that the barrier on Pt 1 / MnO 2 −R (0.92 eV) is lower than that on Pt 1 /MnO 2 (1.21 eV) because of the formation of OVs adjacent to Pt 1 . In the cleavage step of the C−H bond, the CH 4 transfers one H atom to the adjacent O atom.…”
Section: Dft Studiesmentioning
confidence: 99%
“…It is known that the layered-double-hydroxide (LDH) materials developed by Zhang et al have attracted extensive attention for photocatalysis and photothermal catalysis. They synthesized CoFe-based catalysts by H 2 reduction of CoFeAl LDH nanosheets at 300–700 °C . The reduction temperature was found crucial in the surface chemical composition and morphology of the catalysts.…”
Section: Photothermal Catalysis For Environmental Applicationsmentioning
confidence: 99%